High-Speed Resistance Training in Elderly Women: Effects of Cluster Training Sets on Functional Performance and Quality of Life (Vol 110 Pg 216 2018 - Garcia-Hermoso, A (PERGAMON-ELSEVIER SCIENCE LTD, 2019)
Sin Resumen Disponible